2016
DOI: 10.1371/journal.pone.0153039
|View full text |Cite|
|
Sign up to set email alerts
|

Atheists and Agnostics Are More Reflective than Religious Believers: Four Empirical Studies and a Meta-Analysis

Abstract: Individual differences in the mere willingness to think analytically has been shown to predict religious disbelief. Recently, however, it has been argued that analytic thinkers are not actually less religious; rather, the putative association may be a result of religiosity typically being measured after analytic thinking (an order effect). In light of this possibility, we report four studies in which a negative correlation between religious belief and performance on analytic thinking measures is found when rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
175
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 42 publications
12
175
3
Order By: Relevance
“…Nevertheless, the present study did find evidence that analytic cognitive style is negatively associated with both religious belief and paranormal belief, which is consistent with earlier research (Pennycook et al, 2015;Pennycook, Ross, Koehler, & Fugelsang, 2016). These contrasting results leave us with a question: why did we find associations with religious belief and paranormal belief, but not delusional ideation?…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the present study did find evidence that analytic cognitive style is negatively associated with both religious belief and paranormal belief, which is consistent with earlier research (Pennycook et al, 2015;Pennycook, Ross, Koehler, & Fugelsang, 2016). These contrasting results leave us with a question: why did we find associations with religious belief and paranormal belief, but not delusional ideation?…”
Section: Discussionsupporting
confidence: 90%
“…Non-religious participants, on the other hand, appear to be less prone to any of these intuitions. Moreover, these differences are not accounted for by differences in analytic thinking, which in previous research has been shown to be related to lower religious belief (see Pennycook et al, 2012;Pennycook et al, 2016;Shenhav et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Analytic thinking. Previous research has linked analytic thinking to religious disbelief (Gervais & Norenzayan, 2012, Study 1;Pennycook et al, 2012;Pennycook et al, 2016;Shenhav, Rand, & Greene, 2012). Similarly, religious participants tend to score lower on analytic thinking measures than the nonreligious.…”
Section: Anthropomorphism (Idaq)mentioning
confidence: 83%
See 1 more Smart Citation
“…Stanovich (e.g., 2004;2009b) has argued that thinking disposition is an underappreciated determinant of psychological outcomes. Recent research has supported the idea that cognitive style plays a consequential role in psychological domains that are of some general import (Pennycook, Fugelsang, & Koehler, 2015b): e.g., creativity (Barr, Pennycook, Stolz, & Fugelsang, 2014), moral judgments and values (Paxton, Unger, & Greene, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014b;Rozyman, Landy, & Goodwin, 2014), religious belief (Gervais & Norenzayan, 2012;Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2016;Shenhav, Rand, & Greene, 2012), bullshit receptivity (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2015), and even Smartphone technology use (Barr, Pennycook, Stolz, & Fugelsang, 2015 …”
Section: Individual Differences In Analytic Thinkingmentioning
confidence: 99%